Composite adhesives comprising polymeric nanoparticles

The existing bonding is solved by using composite adhesives of polymer nanoparticles with glass transition temperatures below room temperature and shells with high glass transition temperatures in electronic devices, combined with methacrylate-based matrix and crosslinking agents. The problem of insufficient adhesion and drop resistance of the agent under deformation and impact conditions has achieved good mechanical durability and shear deformation resistance.

CN119256028APending Publication Date: 2025-01-033M INNOVATIVE PROPERTIES CO
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202380041666.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-10-07
Filing Date
2023-05-22
Publication Date
2025-01-03

AI Technical Summary

Technical Problem

Existing pressure-sensitive adhesives are difficult to maintain good adhesion and drop resistance under deformation and impact conditions in electronic equipment, especially when equipment simplification and mechanical durability requirements increase, it is difficult to achieve anti-shear resistance. and impact resistance.

Method used

Using composite adhesive containing polymer nanoparticles with glass transition temperature below room temperature and shell with high glass transition temperature, combined with methacrylate-based matrix and crosslinking agent to form good adhesion and impact resistance adhesive.

Benefits of technology

A composite adhesive that maintains adhesion under deformation and impact conditions is realized, which improves the mechanical durability and shear deformation resistance of electronic equipment, and enhances the overall performance of the equipment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119256028A_ABST
    Figure CN119256028A_ABST
Patent Text Reader

Abstract

A composite adhesive composition is described herein. The composition comprises: a plurality of polymeric nanoparticles dispersed in a (meth) acrylate-based matrix; and the (meth) acrylate-based matrix is derived from C1 to C12 (meth) acrylate monomers and (meth) acrylate macromonomers. In some embodiments, these composite adhesives exhibit good impact resistance and good dynamic shear resistance. In one embodiment, an ionic liquid is added to the composite adhesive to achieve electrical exfoliation.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to an impact resistant adhesive comprising a (meth)acrylate-based matrix having a plurality of polymer nanoparticles dispersed therein. Summary of the invention

[0002] In electronic devices, especially mobile electronic devices (e.g., handheld or wearable electronic devices), pressure sensitive adhesives (PSAs) are generally used to bond cover glass (or lenses) to underlying display modules, touch sensors to cover glass and displays, or lower components of displays to housings. For these applications (often referred to as electronic device bonding or e-bonding), PSAs should have sufficiently strong adhesive strengths to properly maintain good adhesion to these components, not only when the mobile electronic devices are working under normal conditions, but also when they are deformed (e.g., bent, folded, flexed) by external forces, subjected to traumatic forces (e.g., mobile electronic devices fall onto hard surfaces), or subjected to extreme environmental conditions (e.g., high temperature conditions and / or high humidity conditions). Regarding deformation, when a user sits on a chair with an electronic device in their pocket or their buttocks pressing down on the electronic device, components of the electronic device may be deformed. Under such conditions, the pressure sensitive adhesive should have an adhesive strength sufficient to maintain, for example, adhesion to the cover glass (sometimes referred to as anti-wrinkling). With respect to traumatic forces, the pressure sensitive adhesive should have sufficient drop or impact resistance so that the pressure sensitive adhesive maintains adhesion of the components even when a large momentary impact is applied to the mobile electronic device when the mobile electronic device is dropped.

[0003] Given the electronics industry trends toward device simplification (i.e., combining layers and / or layer functions) and reducing bond area and overall device thickness (and in addition requiring enhanced mechanical durability), there is an increasing need for adhesive tapes that have good adhesion to device substrates, good impact / drop resistance, and adequate shear resistance. Adhesives that achieve this balance of opposing properties are needed.

[0004] In one aspect, a composition is disclosed. The composition comprises: (i) a plurality of polymer nanoparticles, wherein the polymer nanoparticles comprise an interior region and an outer shell, wherein the interior region comprises a polymer having a glass transition temperature below room temperature, and the outer shell comprises a polymer having a glass transition temperature of at least 50° C.; and (ii) a polymerizable matrix comprising: (a) a (meth)acrylate macromonomer, wherein the (meth)acrylate macromonomer comprises a poly(ethylene oxide) group, a poly(propylene oxide) group, a poly(ethylene oxide-co-propylene oxide), a poly(tetramethylene oxide) group, or a combination thereof; (b) a C1 to C 12one or more of (meth)acrylate monomers; (c) a crosslinking agent; and (d) 0 to up to 7 weight percent of a hydroxyl-containing (meth)acrylate monomer.

[0005] In another aspect, a composition is disclosed. The composition comprises: (i) a plurality of polymer nanoparticles, wherein the polymer nanoparticles comprise an interior region and an outer shell, wherein the interior region comprises a polymer having a glass transition temperature below room temperature, and the outer shell comprises a polymer having a glass transition temperature of at least 50° C.; and (ii) a matrix derived from: (a) a (meth)acrylate macromonomer, wherein the (meth)acrylate macromonomer comprises a poly(ethylene oxide) group, a poly(propylene oxide) group, a poly(ethylene oxide-co-propylene oxide), a poly(tetramethylene oxide) group, or a combination thereof; (b) a C1 to C2 12 one or more of (meth)acrylate monomers; (c) a crosslinking agent; and (d) 0 to up to 7 weight percent of a hydroxyl-containing (meth)acrylate monomer.

[0006] In another aspect, an adhesive article is described. The adhesive article comprises a composite adhesive composition derived from one of the above compositions, wherein the composite adhesive composition is disposed on a substrate.

[0007] In yet another embodiment, a method of making an adhesive article is described. The method comprises:

[0008] (i) obtaining a polymerizable matrix, the polymerizable matrix comprising:

[0009] (a) a (meth)acrylate macromonomer, wherein the (meth)acrylate macromonomer comprises a poly(ethylene oxide) group, a poly(propylene oxide) group, a poly(ethylene oxide) group,

[0010] -co-propylene oxide), poly(tetramethylene oxide) groups, or combinations thereof;

[0011] (b) C1 to C 12 One or more of (meth)acrylate monomers;

[0012] (c) a cross-linking agent; and

[0013] (d) 0 to up to 7 wt % of a hydroxyl-containing (meth)acrylate monomer; and

[0014] (ii) adding a plurality of polymer nanoparticles to a polymerizable matrix to form a composition.

[0015] In yet another embodiment, a method of making an adhesive article is described. The method comprises:

[0016] (i) obtaining a polymerizable matrix, the polymerizable matrix comprising:

[0017] (a) a (meth)acrylate macromonomer, wherein the (meth)acrylate macromonomer comprises a poly(ethylene oxide) group, a poly(propylene oxide) group, a poly(ethylene oxide-co-propylene oxide), a poly(tetramethylene oxide) group, or a combination thereof;

[0018] (b) C1 to C 12 One or more of (meth)acrylate monomers;

[0019] (c) a cross-linking agent; and

[0020] (d) 0 to up to 7 wt % of a hydroxyl-containing (meth)acrylate monomer; and

[0021] (ii) at least partially polymerizing the polymerizable matrix to form an at least partially polymerized composition, and

[0022] (iii) adding a plurality of polymer nanoparticles, wherein the polymer nanoparticles include an inner region and an outer shell, the inner region comprising a polymer having a glass transition temperature below room temperature,

[0023] And the shell comprises a polymer having a glass transition temperature of at least 50°C.

[0024] The above summary of the invention is not intended to describe every embodiment. The details of one or more embodiments of the present invention are also listed in the following detailed description. Other features, objectives and advantages will be apparent from this specification and claims. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Embodiments of the present disclosure are shown by way of example in the accompanying drawings, which are for illustration purposes only and are not drawn to scale.

[0026] Figure 1 is a schematic cross-sectional view of a multilayer adhesive article including a composite adhesive layer according to one embodiment of the present disclosure; and

[0027] Figure 2 is a schematic cross-sectional view of a composite adhesive layer according to one embodiment of the present disclosure.

[0028] Figure 3A is a top view of the test specimen used for the random free fall test, Figure 3B is a schematic side view of the test sample.

[0029] Figure 4 is a schematic cross-sectional view of a multilayer adhesive article including a composite adhesive layer according to one embodiment of the present disclosure.

[0030] Figure 5 is a schematic cross-sectional view of a multilayer adhesive article including a composite adhesive layer according to one embodiment of the present disclosure. DETAILED DESCRIPTION

[0031] As used herein, the term

[0032] “A,” “an,” and “the” are used interchangeably and refer to one or more; and

[0033] "And / or" is used to indicate that one or both of the stated situations may occur, for example, A and / or B includes (A and B) and (A or B);

[0034] "Cross-linking" refers to the joining of two preformed polymer chains using chemical bonds or chemical groups in order to increase the modulus of the material; and

[0035] "(Meth)acrylate" refers to a compound containing an acrylate (CH2=CHCOOR) or methacrylate (CH2=CCH3COOR) structure or a combination thereof.

[0036] As used herein, the term "macromer" refers to a monomer having a polymerizing group. Macromer is a subset of the term "monomer."

[0037] The term "monomer unit" refers to the reaction product of the polymerizable components (i.e., monomers (including macromonomers)) in the (meth)acrylate copolymer. For example, the monomer unit of acrylic acid

[0038] yes Wherein an asterisk (*) indicates a site of attachment to another group, such as another monomer unit or a terminal group in a (meth)acrylate copolymer.

[0039] The term "(meth)acrylate macromonomer" refers to a monomer having a single (meth)acryloyloxy group (i.e., a group having the formula CH2=CR-(CO)-O-, where R is hydrogen or methyl) plus a poly(ethylene oxide) group, a poly(propylene oxide) group, a poly(ethylene oxide-co-propylene oxide) group, or a poly(tetramethylene oxide) group.

[0040] The term "poly(ethylene oxide) group" refers to a group containing at least 3 ethylene oxide (-(C2H4O)-) groups, and the term "poly(propylene oxide) group" refers to a group containing at least 3 propylene oxide (-(C3H6O)-) groups.

[0041] The term "poly(ethylene oxide-co-propylene oxide) group" contains at least three groups including at least one ethylene oxide group and at least one propylene oxide group. The poly(ethylene oxide-co-propylene oxide) group is a copolymer group.

[0042] The term "poly(tetramethylene oxide) (meth)acrylate macromonomer" refers to a monomer having a single (meth)acryloyloxy group (i.e., a group of formula CH2=CR-(CO)-O-, where R is hydrogen or methyl) plus a poly(tetramethylene oxide) group containing at least three -(C4H8O)- groups. The term "poly(tetramethylene oxide)" may be used interchangeably with the terms "poly(tetramethylene oxide)" and "poly(tetramethylene glycol)".

[0043] Also herein, the recitations of ranges by endpoints include all numbers subsumed within that range (eg, 1 to 10 includes 1, 2, 3, 4, 5, 6, 7, 8, 9, and 10).

[0044] Additionally, the expression "at least" followed by a number herein includes the listed number and all larger numbers (for example, "at least 1" includes at least 2, at least 4, at least 6, at least 8, at least 10, at least 25, at least 50, at least 100, etc.).

[0045] The adhesive of the present disclosure is a composite material comprising a plurality of polymer nanoparticles dispersed in a (meth)acrylate-based matrix.

[0046] Polymer Nanoparticles

[0047] The particles of the present disclosure are polymers comprising at least two different polymer regions (internal polymer region and shell). The interior of the particle comprises a polymer having a glass transition temperature (Tg) lower than room temperature, and the shell of the particle comprises a polymer with a high Tg. Although not wishing to be limited by theory, it is believed that the low Tg polymer interior can absorb impact forces, and the harder shell enables the particles to be well dispersed in the matrix. The Tg of the particle can be measured, for example, by using differential scanning calorimetry (DSC). If the particle is composed of a single polymer, then as long as the amount of the polymer in the matrix is ​​sufficient (e.g., greater than 10 wt % or even 5 wt %), a peak should appear in the analysis of each single polymer.

[0048] The polymer particles of the present disclosure are nanostructured, which means that the maximum dimension (e.g., diameter) is less than 900 nanometers, 800 nanometers, 750 nanometers, 500 nanometers, 400 nanometers, 350 nanometers, or even 300 nanometers (nm). In one embodiment, the average particle diameter of the particles is at least 20nm, 50nm, 100nm, 150nm, or even 170nm and at most 500nm, 400nm, 350nm, 300nm, 250nm, or even 200nm. The particle size can be measured using techniques known in the art (such as a particle size analyzer (such as a Malvern Zetasizer) or a microscope (such as a scanning electron microscope) using calibration standards). In one embodiment, the average size of the internal polymer region is at least 10nm, 20nm, or even 50nm and at most 75nm, 100nm, 200nm, 300nm, 400nm, or even 500nm. The size of the internal polymer region can be measured using techniques known in the art (such as a transmission electron microscope).

[0049] In one embodiment, the polymer of the shell of the polymer particle has a Tg of at least 50° C., 60° C., 70° C., 80° C., 100° C., 120° C., or even 150° C.; and no more than 300° C., 250° C., 200° C., or even 175° C. In one embodiment, the shell comprises poly(methyl methacrylate) or poly(glycidyl methacrylate).

[0050] In one embodiment, the Tg of the interior polymer of the polymer particle is less than 25° C., 23° C., 20° C., 15° C., 10° C., 5° C., 0° C., -10° C., -20° C., -25° C., or even -40° C. and exceeds -120° C., -90° C., -80° C., -75° C., or even -50° C. Exemplary polymers that can be used in the interior of the polymer particle include isoprene homopolymers or butadiene homopolymers, (meth)acrylic acid homopolymers or copolymers derived from (meth)acrylate monomers having 1 to 18 carbons (preferably 4 to 18, or even more preferably 4 to 12 or even 4 to 8 carbon atoms), isoprene-butadiene copolymers, copolymers of isoprene with up to 98% by weight of vinyl monomers, and copolymers of butadiene with up to 98% by weight of vinyl monomers. The vinyl monomer can be styrene, alkylstyrene, acrylonitrile, alkyl (meth) acrylate, or butadiene or isoprene, as long as the polymer produces the necessary low Tg internal part. Multifunctional monomers can be used during the polymerization of the internal polymer or grafted onto the internal polymer to introduce sites for partial or complete crosslinking of the polymer. Such multifunctional (e.g., difunctional or trifunctional) monomers include poly (meth) acrylates of polyols, such as butanediol di (meth) acrylate and trimethylolpropane trimethacrylate; divinylbenzene; trivinylbenzene; and triallyl cyanurate; the addition of these functional groups can cause the shell to be crosslinked into a polymeric matrix. Other monomers used for polymer crosslinking include unsaturated functional monomers, such as anhydrides of unsaturated carboxylic acids, anhydrides of unsaturated carboxylic acids and unsaturated epoxides, maleic anhydride, (meth) acrylic acid and glycidyl methacrylate. Crosslinking can also be performed by using the inherent reactivity of monomers (e.g., diene monomers).

[0051] In one embodiment, reactive functional groups present on the exterior of the nanoparticles, such as hydroxyl, glycidyl or acid groups, can be functionalized, for example, by reaction with an alkyl acetoacetoxy group, such as tert-butyl acetoacetoxy.

[0052] In one embodiment, the nanoparticles are core-shell particles comprising a lower Tg polymer core surrounded by a higher Tg polymer shell.

[0053] Exemplary shells of the present disclosure include styrene homopolymers, alkylstyrene homopolymers or methyl methacrylate homopolymers, or copolymers including at least 70% by weight of one of the above monomers and at least one comonomer, another alkyl (meth) acrylate, vinyl acetate and / or acrylonitrile. As known in the art, the shell can be functionalized by grafting or introducing unsaturated functional monomers (such as anhydrides of unsaturated carboxylic acids, anhydrides of unsaturated carboxylic acids and unsaturated epoxides) as comonomers during polymerization. For example, maleic anhydride, (meth) acrylic acid glycidyl methacrylate, hydroxyethyl methacrylate and alkyl (meth) acrylamide can be used. In one embodiment, the core-shell particles include a polystyrene shell and / or a copolymer with a polymethyl methacrylate (PMMA) shell. The shell can also contain an imide functional group by copolymerizing with maleimide or by chemically modifying PMMA with primary amines. Advantageously, the molar concentration of the imide functional group is 30% to 60% (relative to the entire shell).

[0054] In one embodiment, the core-shell particles comprise a poly(methyl methacrylate) shell and a poly(butadiene-co-styrene) interior portion or core.

[0055] In one embodiment, the core-shell particles comprise more than one shell.There are also core-shell copolymers having two shells, one shell made of polystyrene and the other shell on the outside made of PMMA.

[0056] In one embodiment, the outermost shell in contact with the (meth)acrylic resin comprises a polymer having a Tg greater than 25°C or even 50°C.

[0057] In one embodiment, the core-shell ratio is in the weight range of between 10 / 90 and 90 / 10, between 40 / 60 and 90 / 10, between 60 / 40 and 90 / 10, or even between 70 / 30 and 85 / 15.

[0058] Core-shell particles comprising an elastomeric core can be made using techniques known in the art. See, for example, EP 2 465 882 B1 (Navarro et al.). Such particles can also be commercially available under the trade names "CLEASTSTRENGTH XT100" and "W300" from Arkema, Cedex, France; "KANE ACE M731" and "KANE ACE B-564" from Kaneka Corp., Belgium; and "PARALOID EXL-2691J" from Dow Chemical Co., Midland, MI., Michigan.

[0059] In the present disclosure, a plurality of polymer nanoparticles are dispersed in a (meth)acrylate-based matrix to form a composite adhesive.

[0060] (Meth)acrylate matrix

[0061] The matrix of the adhesive of the present disclosure is a (meth)acrylate-based matrix derived from a (meth)acrylate macromonomer and a second (meth)acrylate monomer.

[0062] The (meth)acrylate macromonomer contained in the polymerizable component used to form the (meth)acrylate-based matrix has a (meth)acryloyloxy group plus (i) a poly(ethylene oxide) group, (ii) a poly(propylene oxide) group, (iii) a poly(ethylene oxide-co-propylene oxide) group, the latter three of which may also be referred to as a poly(ethylene glycol), a poly(propylene glycol) or a poly(ethylene glycol-co-propylene glycol) group, (iv) a poly(tetrahydrofuran) group, or (v) a combination thereof. If the macromonomer contains a poly(ethylene oxide) group, it may be referred to as a poly(ethylene oxide) (meth)acrylate. If the macromonomer contains a poly(propylene oxide) group, it may be referred to as a poly(propylene oxide) (meth)acrylate. If the macromonomer contains a poly(ethylene oxide-co-propylene oxide) group, it may be referred to as a poly(ethylene oxide-co-propylene oxide) (meth)acrylate, which is a copolymer. If the macromonomer comprises a poly(tetrahydrofuran) group, it may be referred to as poly(tetrahydrofuran) (meth)acrylate.

[0063] The (meth)acrylate macromonomers typically have a number average molecular weight in the range of 350 to 10,000 Daltons. For example, the (meth)acrylate macromonomers have a number average molecular weight of no more than 10,000 Daltons, 8000 Daltons, 6000 Daltons, 4000 Daltons, 2000 Daltons, 1000 Daltons, 800 Daltons, 650 Daltons or even 500 Daltons. The number average molecular weight can be determined by gel permeation chromatography using techniques known in the art.

[0064] The (meth)acrylate macromonomers typically have a Tg of no more than -10°C (as measured using a homopolymer of the macromonomer). For example, the glass transition temperature may be no more than -10°C, -20°C, -30°C, or even -40°C. In one embodiment, the Tg is less than -70°C or even -80°C. This low Tg of the macromonomer imparts conformability and flexibility to the (meth)acrylate copolymer and the adhesive composition.

[0065] Examples of such commercially available (meth)acrylate macromonomers include poly(ethylene glycol) methyl ether acrylates, such as those having a reported number average molecular weight (Mn) of 480 Daltons (available from Sigma-Aldrich), and poly(propylene glycol) acrylates, such as those having a reported number average molecular weight of 475 Daltons (available from Sigma-Aldrich). Other suitable macromonomers are available from Geo Specialty Chemicals, Ambler, PA, under the tradename BISOMER, such as BISOMER PPA6 (poly(propylene glycol) acrylate having a reported number average molecular weight of 420 Daltons), BISOMER PEM63P HD (a mixture of poly(ethylene glycol) methacrylate and poly(propylene glycol) having a reported number average molecular weight of 524 Daltons), BISOMER PPM5LI (poly(propylene glycol) methacrylate having a reported number average molecular weight of 376 Daltons), BISOMER PEM6 LD (poly(ethylene glycol) methacrylate having a reported number average molecular weight of 350 Daltons), BISOMER MPEG350MA (methoxy poly(ethylene glycol) methacrylate having a reported number average molecular weight of 430 Daltons), and BISOMER MPEG550MA (methoxy poly(ethylene glycol) methacrylate having a reported number average molecular weight of 628 Daltons). Other suitable macromonomers are available from Miwon Specialty Chemical Company, Gyeonggi-do, Korea, under the trade designation MIRAMER, such as MIRAMER M193MPEG600MA (methoxy poly(ethylene glycol) methacrylate having a reported number average molecular weight of 668 Daltons), MIRAMER M164 (nonylphenol poly(ethylene glycol) acrylate having a reported number average molecular weight of 450 Daltons), MIRAMER M1602 (nonylphenol poly(ethylene glycol) acrylate having a reported number average molecular weight of 390 Daltons), and MIRAMER M166 (nonylphenol poly(ethylene glycol) acrylate having a reported number average molecular weight of 626 Daltons). Other suitable macromonomers are available from Sans Esters Corporation, New York, NY, such as MPEG-A400 (methoxy poly(ethylene glycol) acrylate having a reported number average molecular weight of 400 Daltons) and MPEG-A550 (methoxy poly(ethylene glycol) acrylate having a reported number average molecular weight of 550 Daltons). Various combinations of such macromonomers may be used if desired.

[0066] Macromonomers having poly(tetrahydrofuran) groups can be prepared, for example, by polymerizing tetrahydrofuran using a cationic polymerization reaction. More specifically, the polymerization reaction can be carried out at room temperature (e.g., 20° C. to 25° C.) using triflate as an initiator to form an intermediate (A), wherein n is equal to the number of -CH2CH2CH2CH2O- groups. The intermediate (A) is then reacted with hydroxybutyl acrylate in the presence of N,N-diisopropylethylamine to form a poly(tetrahydrofuran) (meth)acrylate macromonomer. The weight average molecular weight of the poly(tetrahydrofuran) (meth)acrylate macromonomer is typically in the range of 350 Daltons to 10,000 Daltons, which can be determined using known methods (such as gel permeation chromatography) with polystyrene as a standard. If the molecular weight is higher, the macromonomer may not be miscible with other components in the polymerizable composition and / or may crystallize before, during, or after the polymerization of the matrix. In many embodiments, the poly(tetramethyleneimine) (meth)acrylate macromonomer has a weight average molecular weight of at least 500, 600, 800, 1,000, 2,000, or even 3,000 Daltons, and at most 10,000, 8,000, 6,000, 5,000, or even 3,000 Daltons.

[0067] The second (meth)acrylate monomer in the polymerizable matrix is ​​C1 to C 12 (Meth)acrylate monomers. Available C1 to C 12The (meth)acrylate monomers include at least one monomer selected from the group consisting of monofunctional (meth)acrylates of linear, branched and / or cyclic non-tertiary alkyl alcohols, the alkyl groups of which contain at least 1, 2, 3, 4, 5, 6, 7 or even 8 carbon atoms; and up to 10, 11, or even 12 carbon atoms. In one embodiment, the (meth)acrylate monomers contain 1 to 12 carbon atoms. Exemplary second (meth)acrylate monomers include methyl (meth)acrylate, ethyl (meth)acrylate, n-propyl (meth)acrylate, isopropyl (meth)acrylate, 2-methylbutyl acrylate, n-butyl acrylate, isobutyl acrylate, tert-butyl (meth)acrylate, n-pentyl (meth)acrylate, isopentyl (meth)acrylate, n-hexyl (meth)acrylate, isohexyl (meth)acrylate, cyclohexyl (meth)acrylate, phenyl (meth)acrylate, n-octyl (meth)acrylate, isooctyl (meth)acrylate, 2-octyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, decyl (meth)acrylate, lauryl (meth)acrylate, 2-propylheptyl (meth)acrylate, isobornyl (meth)acrylate, benzyl (meth)acrylate, nonyl acrylate, isophorol (meth)acrylate, dodecyl (meth)acrylate, and any combination or mixture thereof.

[0068] In one embodiment, the second (meth) acrylate monomer for the matrix is ​​copolymerized with a polar copolymerizable monomer. The polar copolymerizable monomer can be an acid functional or non-acid functional polar monomer, such as acrylic acid, hydroxyethyl acrylate, N-methyl acrylamide, or any monomer having a side chain containing at least one of the following substances: alcohol, carboxylic acid, amine, amide, imide, thiol, ester, phosphate, and combinations thereof. Exemplary polar monomers include: acrylic acid, methacrylic acid, itaconic acid, fumaric acid, crotonic acid, citraconic acid and maleic acid, hydroxyalkyl acrylates, acrylamide and substituted acrylamides (such as (meth) acrylic acid N, N-dialkylaminoalkyl esters or tert-octylacrylamide), acrylamide and substituted acrylamides, lactams and substituted lactams, β-carboxyethyl acrylate, N-vinyl-2-pyrrolidone, N-vinyl caprolactam, acrylonitrile, and any combination or mixture thereof.

[0069] When copolymerized with strong polar monomers, the second (meth) acrylate monomer generally accounts for at least about 75 weight % of the polymerizable monomer composition for substrate. When copolymerized with medium polar monomers, (meth) acrylate monomer generally accounts for at least about 50 weight % of the polymerizable monomer composition for substrate. Strong polar monomers include monoolefinic monocarboxylic acids and dicarboxylic acids, hydroxyalkyl acrylates, cyanoalkyl acrylates, acrylamides or substituted acrylamides, or from medium polar monomers, such as N-vinyl pyrrolidone, acrylonitrile, vinyl chloride or diallyl phthalate. Strong polar monomers preferably account for up to about 25 weight % of the polymerizable monomer composition for substrate, more preferably up to about 15 weight %. Medium polar monomers preferably account for up to about 30 weight % of the polymerizable monomer composition for substrate, more preferably from about 5 weight % to about 30 weight %.

[0070] Additional monomers may be added to the polymerizable matrix composition to modify the properties of the matrix in the adhesive, such as non-polar monomers. The non-polar monomer may be a non-polar ethylenically unsaturated monomer selected from monomers containing hydrocarbon side chains. Examples of suitable non-polar comonomers include 3,3,5-trimethylcyclohexyl acrylate, cyclohexyl acrylate, tert-butyl acrylate, methyl methacrylate, ethyl methacrylate, and combinations thereof.

[0071] A crosslinking agent is used to generate a three-dimensional polymer network and to achieve high internal strength of the (meth)acrylate matrix in the adhesive. Available crosslinking agents include photosensitive crosslinking agents, which are activated by ultraviolet (UV) light. Available crosslinking agents include: multifunctional (meth)acrylates, triazines, and combinations thereof. Exemplary crosslinking agents include substituted triazines, such as 2,4-bis(trichloromethyl)-6-(4-methoxyphenyl)-s-triazine, 2,4-bis(trichloromethyl)-6-(3,4-dimethoxyphenyl)-s-triazine, and chromophore-substituted halogenated-s-triazines disclosed in U.S. Patents 4,329,384 and 4,330,590 (Vesley). Other useful crosslinking agents include multifunctional alkyl acrylate monomers such as trimethylolpropane triacrylate, pentaerythritol tetraacrylate, 1,2-ethylene glycol diacrylate, 1,4-butanediol diacrylate, 1,6-hexanediol diacrylate, and 1,12-dodecyl alcohol diacrylate. Various other crosslinking agents with different molecular weights between (meth)acrylate functional groups are also useful.

[0072] In the present disclosure, (meth)acrylate (such as C1 to C 12(Meth) acrylate) monomers, (meth) acrylate macromonomers and any optional comonomers are polymerized to form a (meth) acrylate matrix. The (meth) acrylate matrix should be derived from a hydroxyl-containing (meth) acrylate monomer of no more than 7 wt %. For example, no more than 7 wt %, 6 wt %, 5 wt %, 4 wt %, 2 wt %, 1 wt % or even 0.5 wt % or even no hydroxyl-containing (meth) acrylate monomer is used in the polymerization of the (meth) acrylate matrix. Exemplary hydroxyl-containing (meth) acrylate monomers include (meth) acrylates containing C1 to C20 alkyl groups with at least one hydroxyl group, such as (meth) acrylate 2-hydroxyethyl, (meth) acrylate 4-hydroxybutyl, (meth) acrylate 2-hydroxypropyl, (meth) acrylate 2-hydroxybutyl and (meth) acrylate 6-hydroxyhexyl. As shown in the example section, even the presence of a large amount of hydroxyl-containing (meth) acrylate monomers (e.g., 10phr or 20phr) also produces poor adhesion and dynamic shear properties of the resulting adhesive composition.

[0073] In one embodiment, the polymer of the matrix is ​​derived from at least 40%, 50%, 60%, 70% or even 75%, up to 80%, 85%, 90%, 95%, 97% or even 99.5% by weight of C1 to C2 monomers relative to the other monomers. 12 (Meth)acrylate monomers. C1 to C 12 The amount of (meth)acrylate monomers relative to other comonomers is relatively high, providing sufficiently large adhesion at low temperatures (e.g., below room temperature) and / or at relatively high peel rates (e.g., >12 in / min). It has been found that the use of large amounts of high chain length (meth)acrylate monomers (e.g., C18) results in a matrix with a shear modulus that is too low and too soft to achieve the desired performance characteristics. Similarly, higher carbon chain length acrylates do not have sufficient compatibility with polymer nanoparticles to sufficiently increase the modulus to improve their performance. Since methacrylate monomers (e.g., methyl methacrylate) can increase the Tg of the copolymer matrix and reduce its molecular weight (and thus limit performance) compared to their acrylate counterparts (e.g., methyl acrylate), in one embodiment, the polymerizable matrix (or a matrix derived therefrom) contains less than 10 wt%, 5 wt%, 3 wt%, 2 wt%, 1 wt%, or even 0.5 wt%, or even undetectable amounts of C1 to C 12 Methacrylate monomers.

[0074] Optionally, the polymer of the matrix comprises at least 0.5 wt%, 1.0 wt%, 2.5 wt%, 5 wt%, 8 wt%, or even 10 wt%, up to 15 wt%, 18 wt%, 20 wt%, 25 wt%, 30 wt%, 35 wt%, 40 wt%, 45 wt% or even 50 wt% polar monomer relative to other monomers present in the (meth)acrylate-based matrix.

[0075] In one embodiment, the (meth)acrylate-based matrix contains at least 1 wt%, 1.5 wt%, 2 wt%, 5 wt%, 10 wt%, 15 wt%, 20 wt%, 25 wt%, 30 wt%, or even 35 wt% of (meth)acrylate macromers. In one embodiment, the (meth)acrylate-based matrix contains up to 60 wt%, 55 wt%, 50 wt%, 45 wt%, 40 wt%, 30 wt%, or even 20 wt%. The amount of (meth)acrylate macromers used is based on the total weight of polymerizable components (e.g., monomers) in the matrix.

[0076] In one embodiment, the crosslinking agent can be added at a level of at least 0.01, 0.1, 0.5, 1.0, or even 1.5 parts solids, up to 2, 3, 4, 5, 6, 8, or even 10 parts solids per 100 parts solids relative to the weight of all polymerizable components used in preparing the (meth)acrylate-based matrix. In another embodiment, an initiator is used that will produce crosslinks in situ by abstracting hydrogens from the polymers in the matrix, thereby allowing the (meth)acrylate-based matrix to crosslink. Typically, the crosslinking initiator is used at a concentration of at least 0.01, 0.1, 0.5, 1.0, 1.5, or even 2 parts solids, up to 3, 4, 5, 6, 8, or even 10 parts solids per 100 parts solids relative to the weight of all monomers used in preparing the (meth)acrylate-based matrix.

[0077] In one embodiment, the polymer in the (meth)acrylate matrix has a weight average molecular weight of at least 100,000, 200,000, 300,000, 400,000, 500,000, 750,000 or even 1,000,000 g / mole, up to 20,000,000, 25,000,000 or even 30,000,000 g / mole. The molecular weight of the polymer can be determined by gel permeation chromatography as known in the art. The polymer typically has a molecular weight dispersity, which can be calculated as the weight average molecular weight to number average molecular weight of the polymer. The intrinsic viscosity is related to the molecular weight of the polymer, but also includes other factors, such as the concentration of the polymer. In the present disclosure, the intrinsic viscosity of the polymer can be at least 0.4, 0.45, 0.5, 0.6, 0.7 or even 0.8, at most 0.7, 0.8, 1.0, 1.2, 1.4, 1.6, 1.8 or even 2, 3, as measured in ethyl acetate at a concentration of 0.15 grams per deciliter (g / dL).

[0078] The molecular weight of the polymer in the (meth)acrylate matrix can be controlled using techniques known in the art. For example, during polymerization, a chain transfer agent can be added to the monomer to control the molecular weight. Available chain transfer agents include, for example, those selected from carbon tetrabromide, alcohol, mercaptan, and mixtures thereof. Exemplary chain transfer agents are isooctyl thioglycolate and carbon tetrabromide. Relative to the weight of all monomers used to prepare the (meth)acrylate matrix, based on 100 parts, at least 0.01, 0.05, 0.1, 0.15, 0.2, 0.3 or even 0.4 parts by weight of chain transfer agent can be used, and up to 0.1, 0.2, 0.3, 0.4, 0.5 or even 0.6 parts by weight of chain transfer agent can be used.

[0079] The (meth)acrylate matrix used in the adhesive of the present disclosure can be polymerized by techniques known in the art, including, for example, conventional solvent-free polymerization techniques. Polymerizing the monomers "substantially solvent-free" means using less than 5%, 2%, 1%, or even 0.5% by weight of solvent based on the weight of the monomers, and more preferably no additional solvent is added during polymerization. The term "solvent" refers to both water and conventional organic solvents used in the industry that evaporate during the process.

[0080] Composite adhesives

[0081] The process of preparing a composite adhesive according to at least one embodiment of the present disclosure is described in more detail below.

[0082] The polymerizable matrix comprising a (meth)acrylate macromonomer and a second (meth)acrylate monomer and an optional comonomer can be polymerized by various techniques, wherein photoinitiated bulk polymerization is preferred. An initiator is preferably added to assist in the polymerization of the monomer. The type of initiator used depends on the polymerization method. In a preferred embodiment, a photoinitiator is used to initiate the polymerization. Photoinitiators that can be used to polymerize acrylate monomers include: benzoin ethers, such as benzoin methyl ether or benzoin isopropyl ether; substituted benzoin ethers, such as 2-methyl-2-hydroxypropiophenone; aromatic sulfonyl chlorides, such as 2-naphthalenesulfonyl chloride; and photoactive oxides, such as 1-phenyl-1,2-propanedione-2-(o-ethoxycarbonyl)oxime. An example of a commercially available photoinitiator is "IRGACURE 651" having the formula 2,2-dimethoxy-1,2-diphenylethane-1-one available from Ciba. Generally, the photoinitiator is present in an amount of about 0.005% to 1% by weight based on the weight of the monomer. In another embodiment, a thermal initiator such as, for example, AIBN (azobisisobutyronitrile) and / or a peroxide may be used. The polymerization may be carried out in the presence of at least one free radical initiator. Available free radical UV initiators include, for example, benzophenone.

[0083] In the preferred practice of the present disclosure, polymer nanoparticles are blended with an acrylic syrup (which becomes part of the (meth)acrylate matrix). As used herein, syrup refers to a mixture that has been thickened to a coatable viscosity (i.e., preferably between about 300 and 10,000 centipoise or higher, depending on the coating method used), including mixtures in which monomers are partially polymerized to form syrups and monomer mixtures that have been thickened with fillers such as silica.

[0084] The composite composition of the present disclosure (i.e., comprising polymer nanoparticles, and acrylate monomers or acrylic syrups for forming a (meth)acrylate matrix) can be irradiated with an activated ultraviolet radiation having an ultraviolet (UV) absorbance maximum within the range of 280 nanometers to 425 nanometers to polymerize the monomer components. The UV light source can be of various types. Low-intensity light sources such as black light lamps typically provide an intensity within the range of 0.1 mW / cm2 or 0.5 mW / cm2 (milliwatts / square centimeter) to 10 mW / cm2 (measured according to a procedure approved by the National Institute of Standards and Technology, such as, for example, using a UVIMAP UM 365L-S radiometer manufactured by Electronic Instrumentation & Technology, Inc., Sterling, VA, located in Sterling, Virginia). High-intensity light sources typically provide an intensity greater than 10 mW / cm2, 15 mW / cm2, or 20 mW / cm2, ranging up to 450 mW / cm2 or greater. In some embodiments, the high intensity light source provides an intensity of up to 500mW / cm2, 600mW / cm2, 700mW / cm2, 800mW / cm2, 900mW / cm2, or 1000mW / cm2. The UV light used to polymerize the monomer components can be provided by various light sources, such as light emitting diodes (LEDs), black light lamps, medium pressure mercury lamps, etc., or combinations thereof. The composite composition can also be polymerized with a higher intensity light source purchased from FusionUV Systems Inc., Gaithersburg, MD, USA. The UV acceptance time for polymerization and curing can vary depending on the intensity of the light source used. For example, full curing using a low intensity light process can be completed at an acceptance time in the range of about 30 seconds to 300 seconds; while full curing using a high intensity light source can be completed at a shorter exposure time in the range of about 5 seconds to 20 seconds. Partial curing using a high intensity light source can typically be completed at an acceptance time in the range of about 2 seconds to about 5 seconds or 10 seconds.

[0085] Preferably, the slurry of the present invention is formed by polymerizing the monomer part by free radical initiators known in the art and can be activated by heat or radiation (such as ultraviolet light). In some cases, it may be preferred to add other monomers and other photoinitiators and other additives to the slurry. At least one free radical initiator of an effective amount is added to the (meth) acrylate monomer or slurry containing polymer nanoparticles. The mixture is then applied to a substrate such as a transparent polyester film (which may be optionally coated with a release coating), and then exposed to ultraviolet radiation in a nitrogen-rich atmosphere to form an adhesive. Alternatively, oxygen can be excluded by covering a second layer of release-coated polyester film on the applied adhesive, and then exposed to ultraviolet radiation. Subsequently exposing the adhesive to a second energy source can be used to crosslink or further cure the adhesive. Such energy sources include heat, electron beams, gamma radiation, and high-intensity ultraviolet lamps such as mercury arc lamps.

[0086] In one embodiment, the adhesive of the present disclosure can be prepared by combining polymer nanoparticles with a prepolymerized (meth)acrylate-based matrix comprising a crosslinker, a free radical initiator, and optional additional components described below, and then coating the mixture onto a flat substrate (such as a polymer film). In one embodiment, a plurality of polymer nanoparticles can be pre-dispersed in a monomer solution (such as a (meth)acrylate monomer and a polymer dispersant mixture) to aid in the dispersion of the polymer nanoparticles into the polymerizable matrix. The coated mixture can then be exposed to an energy source (such as a UV radiation source) in a low oxygen atmosphere (i.e., less than 1000 parts per million (ppm), and preferably less than 500 ppm) until polymerization is substantially complete (i.e., less than 10% residual monomer, and preferably less than 5%).

[0087] Alternatively, sufficient oxygen-free atmosphere can be provided by sealing the polymerizable composite composition with, for example, a polymer film. In one embodiment, a film can be covered on the adhesive composition of coating before polymerization. In another embodiment, the adhesive composition is placed in a receiver (which can be optionally sealed), then exposed to energy, such as heat or ultraviolet radiation, so that the adhesive is cross-linked. Then, the adhesive can be distributed from the receiver for use, or the receiver can be sent to a hot melt coater and applied to the substrate, to make adhesive tape or other types of adhesive coating substrates (for example, labels). In the latter case, the receiver material should be hot-melt coated with the adhesive in the receiver, and the receiver material can not adversely affect the desired final properties of the adhesive.

[0088] The adhesive composition may include additional components to affect the performance and / or characteristics of the composition. Such additives include plasticizers, tackifiers, antistatic agents, colorants, antioxidants, pigments (such as carbon black), dyes, fungicides, bactericides, anticorrosive additives (such as benzotriazole derivatives, n-vinyl imidazole, thiourea, 2-(dimethylamino) ethyl acrylate, coumaric acid derivatives or their combinations), organic and / or inorganic filler particles, etc. Such organic fillers include, for example, pre-expanded polymer microspheres, which may or may not include a coating with a metal salt, such as DUALITE E135-040D or MFL HEPTEN. The use of these additives is well known to those skilled in the art. In one embodiment, additives are present in an amount that makes the solid in the curable adhesive composition (or cured adhesive) account for at least 65% by weight of a (meth) acrylate matrix. Therefore, the total amount of additives should be less than 35% by weight, 30% by weight, 25% by weight, 20% by weight, 10% by weight, 5% by weight or even 1% by weight of solid. Certain additives may have lower weight percentages, for example, less than 0.05 weight % of solids or even less than 0.005 weight % of solids of pigment may be added. In some embodiments, such as in the case of inorganic fillers, a large amount of inorganic filler (e.g., greater than 60 weight %, 70 weight %, 80 weight % or even 95 weight % of solids) may be used.

[0089] Exemplary tackifiers include: C5 resins, terpene phenolic resins, (poly)terpenes and rosin esters, hydrogenated hydrocarbon and non-hydrogenated hydrocarbon resins. When used, the tackifier can be added at a level of at least 5, 8, 10 or even 12 parts, and up to 15, 20, 25 or even 30 parts per 100 parts by weight of the total (meth)acrylate based matrix.

[0090] In one embodiment, the adhesive composition comprises an ionic liquid. When reprocessing or recycling the product, the presence of an ionic liquid can be used to promote the peeling (or peelability) of the adhesive. Ionic liquids are unique salts that are liquid at about 100°C or lower temperatures, have negligible vapor pressure and high thermal stability. Ionic liquids are composed of cations and anions and have a melting point of about 100°C or lower temperatures (i.e., liquid at about 100°C or lower temperatures), about 95°C or lower temperatures, or even about 80°C or lower temperatures. Some ionic liquids exist in a molten state even at ambient temperature because their melting points are lower than room temperature, and therefore they are sometimes referred to as ambient temperature molten salts. The spatial volume of the cations and / or anions of the ionic liquid is relatively large, and generally, one and / or both of these ions are organic ions. Ionic liquids can be synthesized by known methods, for example, by methods such as anion exchange or metathesis or by acid-base or neutralization methods.

[0091] The cation of the ionic liquid of the present disclosure can be a nitrogen-containing cation, a phosphonium ion, a sulfonium ion, etc., including various unlocalized heteroaromatic cations, but not limited thereto. The nitrogen-containing cation includes ions such as alkylammonium, imidazolium, pyridinium, pyrrolidinium, pyrrolinium, pyrazinium, pyrimidinium, triazolium, triazinium, quinolinium, isoquinolinium, indolium, quinoxalinium, piperidinium, oxazolinium, thiazolinium, morpholinium, piperazinium, and combinations thereof. Examples of phosphonium ions include phosphonium ions selected from tetraalkylphosphonium, arylphosphonium, alkylarylphosphonium, and combinations thereof. Examples of sulfonium ions include sulfonium ions selected from alkylsulfonium, arylsulfonium, thiophenium, tetrahydrothiophenium, and combinations thereof. The alkyl group directly bonded to the nitrogen atom, phosphorus atom, or sulfur atom may be a linear, branched, or cyclic alkyl group having at least 1, 2, or even 4 carbon atoms and not more than 8, 10, 12, 15, or even 20 carbon atoms. The alkyl group may optionally contain heteroatoms such as O and N and S in the chain or at the end of the chain (e.g., terminal-OH group). The aryl group directly bonded to the nitrogen atom, phosphorus atom, or sulfur atom may be a monocyclic or condensed cyclic aryl group having at least 5, 6, or even 8 carbon atoms and not more than 12, 15, or even 20 carbon atoms. Any position in the structure constituting such a cation may be further substituted by an alkyl group, an alkenyl group, an alkynyl group, a cycloalkyl group, an aryl group, an aralkyl group, an arylalkyl group, an alkoxy group, an aryloxy group, a hydroxyl group, a carbonyl group, a carboxyl group, an ester group, an acyl group, an amino group, a dialkylamino group, an amide group, an imino group, an imide group, a nitro group, a nitrile group, a thioether group, a sulfoxide group, a sulfone group, a halogen atom or the like, and hetero atoms such as oxygen atoms, nitrogen atoms, sulfur atoms and silicon atoms may be contained in the main chain or ring of the structure constituting the cation.

[0092] Specific examples of the cation include N-ethyl-N'-methylimidazolium, N-methyl-N'-butylimidazolium, N-methyl-N-propylpiperidinium, N,N,N-trimethyl-N-propylammonium, N-methyl-N,N,N-tripropylammonium, N,N,N-trimethyl-N-butylammonium, N,N,N-trimethyl-N-methoxyethylammonium, N-methyl-N,N,N-tri(methoxyethyl)ammonium, N,N-dimethyl-N-butyl-N-methoxyethylammonium, N,N-dimethyl-N,N-dibutylammonium, N-methyl-N,N-dibutyl-N-methoxyethylammonium, N-methyl-N,N,N-tributylammonium, ammonium, N,N,N-trimethyl-N-hexylammonium, N,N-diethyl-N-methyl-N-(2-methoxyethyl)ammonium, 1-propyl-tetrahydrothiophenium, 1-butyl-tetrahydrothiophenium, 1-pentyl-tetrahydrothiophenium, 1-hexyl-tetrahydrothiophenium, glycidyltrimethylammonium, N-ethylacryloyl-N,N,N-trimethylammonium, N-ethyl-N-methylmorpholinium, N,N,N-trioctylammonium, N-methyl-N,N,N-trioctylammonium, N,N-dimethyl-N-octyl-N-(2-hydroxyethyl)ammonium, triethylsulfonium, trimethylammonium ethyl acrylate, dimethylaminoethyl methyl acrylate or a mixture thereof.

[0093] The anion of the ionic liquid of the present disclosure can be, for example, sulfate (R-OSO3 - ); sulfonate (R-SO3 - ); carboxylate (R-CO2 - ); phosphate ((RO)2P(=O)O - ); with the formula: BR4 - borate, such as tetrafluoroborate (BF4 - ) and tetraalkylborate; Formula: PR6 - Phosphate, such as hexafluorophosphate (PF6 - ) and hexaalkylphosphate; amide group (R2N - );sulfonamide;methyl anion (R3C - ); methylated compounds, nitrate ions (NO3 - ); nitrite ion (NO2 - );Or halogen ion, such as iodide ion or chloride ion.In the above formula, each R can be independently a hydrogen atom, a halogen atom (fluorine, chlorine, bromine, iodine), a substituted or unsubstituted alkyl group, an alkenyl group, an alkynyl group, a cycloalkyl group, an aryl group, an aralkyl group, an arylalkyl group, an acyl group or a sulfonyl group, etc.Heteroatoms such as oxygen atoms, nitrogen atoms and sulfur atoms can be included in the main chain or ring of the R group, and some or all of the hydrogen atoms on the carbon atoms of the R group can be replaced with fluorine atoms.In the case of multiple R's in the anion, these R's can be the same or different.

[0094] In some embodiments, it is advantageous to use perfluorinated ions, such as perfluorinated anions, to achieve excellent corrosion resistance and electrostripping. However, the use of fluorinated ions should be balanced with the environmental impact of the finished product, as some fluorinated chemicals may be restricted from use due to environmental issues. Examples of anions containing perfluoroalkyl groups that can be used include bis(perfluoroalkylsulfonyl)imide ((RfSO2)2N - ), perfluoroalkyl sulfonate (RfSO3 - ) and tris(perfluoroalkylsulfonyl)methyl anion ((RfSO2)3C - )(wherein Rf represents a perfluoroalkyl group). The carbon number of the perfluoroalkyl group can be, for example, at least 1, 2, 3 or even 4 to at most 8, 10, 12, 15 or even 20. Specific examples of bis(perfluoroalkylsulfonyl)imides include: bis(trifluoromethanesulfonyl)imide, bis(pentafluoroethanesulfonyl)imide, bis(heptafluoropropanesulfonyl)imide, bis(fluorosulfonyl)imide and bis(nonafluorobutanesulfonyl)imide. Specific examples of perfluoroalkylsulfonates include: trifluoromethanesulfonate, pentafluoroethanesulfonate, heptafluoropropanesulfonate, nonafluorobutanesulfonate. Specific examples of tris(perfluoroalkylsulfonyl)methyl anions include tris(trifluoromethanesulfonyl)methyl anions, tris(pentafluoroethanesulfonyl)methyl anions, tris(heptafluoropropanesulfonyl)methyl anions, tris(nonafluorobutanesulfonyl)methyl anions, and combinations thereof. Examples of fluorinated anions that do not include a C-F bond are hexafluorophosphate and bis(fluorosulfonyl)imide. Ionic liquids that do not include a C-F bond include BMIPF6, BMII, DMAEAM FAI, and DMAEAM TCM.

[0095] In some embodiments, the anion of the ionic liquid does not contain any halogen (e.g., fluorine). One such anion is tricyanomethide. Ionic liquids that do not contain any fluorine include BMII and DMAEAM TCM.

[0096] For the ionic liquid composed of the above cations and anions, 1-butyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide, triethylsulfonium bis(trifluoromethanesulfonyl)imide, 1-butyl-3-methylimidazolium hexafluorophosphate, 1-butyl-3-methylimidazolium iodide, ethylpyridinium bis(trifluoromethanesulfonyl)imide, trimethylammonium ethyl acrylate bis(trifluoromethanesulfonyl)imide, dimethylaminoethyl acrylate methyl bis(trifluoromethanesulfonyl)imide, dimethylaminoethyl acrylate methyl bis(fluorosulfonyl)imide, dimethylaminoethyl acrylate methyl tricyanomethyl, and tetraalkylammonium having a hydroxyl functional group and a bis(trifluoromethanesulfonyl)imide counter ion (available under the trade name "FC-5000" from 3M Company, Maplewood, Minnesota (3M) Co., Maplewood, MN)) can be advantageously used as ionic liquids because they have excellent removability during electrostripping due to the reduction in bond strength after power is applied.

[0097] If an ionic liquid is used, the ionic liquid in the composite adhesive may be present at least 0.5 wt%, 1 wt%, 1.5 wt%, or even 2 wt%, and at most 2.5 wt%, 3 wt%, 4 wt%, 5 wt%, 6 wt%, 7 wt%, 8 wt%, or even 9 wt%. Sufficient ionic liquid should be added to achieve electro-stripping, while too much ionic liquid may adversely affect the physical properties of the composite adhesive (such as shear, peel adhesion, and / or the ability to withstand random free fall testing).

[0098] Incorporating ionic liquids into the composite adhesive can enable the composite adhesive to be stripped from the substrate. In one embodiment, the composite adhesive comprises a small amount of acid or is substantially free of acid. In electrical stripping applications, as described below, the amount of acid in the composite adhesive can be advantageously minimized to prevent corrosion of the conductive material. In one embodiment, the composite adhesive comprises less than 1 wt %, 2 wt %, 3 wt %, 4 wt % or even 5 wt % of an acidic monomer (such as acrylic acid), or even does not comprise detectable acidic monomers.

[0099] The selection of ionic liquids for composite adhesives can affect electrostripping. For example, it may be advantageous to select ionic liquids with high electrical conductivity or ionic mobility. Without being limited by theory, it is believed that an increase in the mobility of the ionic liquid in the adhesive is beneficial for electrostripping. Thus, it may be advantageous for the ionic liquid to be highly soluble in the adhesive matrix (i.e., the ionic liquid does not phase separate from the adhesive matrix). High mobility and high electrical conductivity (e.g., having a relative molecular mass of less than 1×10 3In some embodiments, the adhesive thickness can be 10 microns, 25 microns, 50 microns, 60 microns, 70 microns, 80 microns, 90 microns, 100 microns, 150 microns, 200 microns, 250 microns, 300 microns, 400 microns or even 500 microns thick at most. Alternatively, or additionally, it may be advantageous to select an ionic liquid with an electrochemically unstable cation or an anion. Without wishing to be limited by theory, it is believed that an electrochemically unstable cation or anion may produce an increased electrical stripping response. Therefore, it may be advantageous to select a cation composed of an imidazolium derivative or a pyridinium derivative compared to a quaternary ammonium derivative.

[0100] In one embodiment, for environmental reasons, it may be advantageous to select an ionic liquid that does not contain a carbon-fluorine bond. Thus, it may be advantageous to select an ionic liquid containing an inorganic fluorine (such as hexafluorophosphate ion or tetrafluoroborate ion) instead of an ionic liquid containing an organic fluorine (such as bis(trifluoromethylsulfonyl)imide).

[0101] In one embodiment, the composite adhesive disclosed herein is not a foam, which means that the (meth)acrylate-based matrix contains less than 5% by volume of voids, wherein the voids may be obtained by cells formed by gas or due to the incorporation of hollow fillers (such as hollow polymer particles, hollow glass microspheres, or hollow ceramic microspheres).

[0102] Composite adhesive disclosed herein can be advantageously used to prepare a wide range of adhesive tapes and adhesive products. Many of these adhesive tapes and products all contain a backing or release liner for supporting an adhesive layer. As used herein, a backing is a permanent support intended for the final use of an adhesive product. On the other hand, a liner is a temporary support that is not intended for the final use of an adhesive product, but is used to support and / or protect the adhesive product during manufacture or storage. The liner is removed from the adhesive product before the final use of the adhesive product. In order to facilitate easy removal from the adhesive layer, the liner is usually coated with a release coating comprising a release agent. Such release agents are known in the art and are described, for example, in "Handbook of Pressure Sensitive Adhesive Technology," D. Satas, editor, Van Nostrand Reinhold, New York, NY, 1989, pp. 585-600. In one embodiment, the release agent migrates to the surface (on the liner or release coating) to provide suitable release properties. Examples of release agents include urethanes, silicones, and fluorocarbons. Illustrative examples of surface-applied (i.e., topically applied) release agents include: polyvinyl urethanes, such as disclosed in U.S. Pat. No. 2,532,011 (Dahlquist et al.); reactive silicones; fluoropolymers; epoxy silicones, such as disclosed in U.S. Pat. Nos. 4,313,988 (Bany et al.) and 4,482,687 (Kessel et al.); polyorganosiloxane-polyurea segmented copolymers, such as disclosed in European Patent No. 0250248B1 (Leir et al.), and the like.

[0103] In one embodiment, adhesive article is a double-sided tape, characterized in that adhesive is provided on the opposite sides of the backing layer. The adhesive on these two sides (that is, the first adhesive layer and the second adhesive layer) can be the same or different. The backing layer can be a film, a nonwoven web, a paper material or a foam, as further described below. The double-sided tape can include one or two release liners that protect the adhesive surface from contacting the backing layer. In one embodiment, the adhesive layer is arranged between two release liners that can be the same or different. In another embodiment, the adhesive layer is arranged on the backing, and the opposite side of the backing comprises a release agent. The adhesive article is wound up by itself so that the exposed surface of the adhesive layer (opposite to the backing) contacts the release coating backing of the tape roll, for example. In another embodiment, the adhesive is arranged between the backing and the release liner. In some embodiments, adhesive tape and adhesive article do not include a backing, and are therefore self-supporting adhesive layers. Transfer adhesive tape is an example of this type of adhesive article. Transfer adhesive tape (also referred to as transfer tape) has an adhesive layer delivered on one or more release liners. The adhesive layer has no backing therein, so once delivered to the target substrate and the liner removed, only the adhesive is present. Some transfer tapes are multi-layer transfer tapes, which have at least two adhesive layers that may be the same or different. Transfer tapes are widely used in the printing and papermaking industries to make automatic splices of paper webs, and are used by industry and consumers in a variety of bonding, mounting and matting applications.

[0104] In one embodiment, the composite adhesive composition can be easily coated on a carrier film to produce an adhesive coated sheet material cured by ultraviolet radiation. Coating techniques known in the art can be used, such as spraying, overflow coating, blade coating, Meyer rod coating, concave coating and double roller coating. The coating thickness varies with various factors, such as specific applications or coating formulations. The coating thickness considered is at least 10 μm, 20 μm, 25 μm, 30 μm, 40 μm, 50 μm, 60 μm, 75 μm or even 100 μm (micrometer) and at most 125 μm, 150 μm, 200 μm, 250 μm, 300 μm or even 500 μm. In some embodiments, it may be preferred to have a thicker adhesive layer, for example, with better impact resistance. However, thicker adhesives may be more challenging to electrically strip due to having more insulating properties.

[0105] The carrier film may be a flexible or inflexible backing material or a release liner. Exemplary materials that may be used as carrier films for adhesive articles of the present disclosure include, but are not limited to, polyolefins such as polyethylene, polypropylene (including isotactic polypropylene and high impact polypropylene), polystyrene, polyesters including poly(ethylene terephthalate), polyvinyl chloride, poly(butylene terephthalate), poly(caprolactam), polyvinyl alcohol, polyurethane, poly(vinylidene fluoride), cellulose and cellulose derivatives such as cellulose acetate and cellophane, and wovens and nonwovens. Commercially available carrier films include kraft paper (available from Monadnock Paper, Inc.); spunbonded poly(ethylene) and poly(propylene), such as those available under the trade names "TYVEK" and "TYPAR" (available from The Chemours Co.); and porous films available from poly(ethylene) and poly(propylene), such as those available under the trade name "TESLIN" (available from PPG Industries, Inc.) and those available under the trade name "CELLGUARD" (available from Hoechst-Celanese). The carrier film delivers the composite adhesive of the present disclosure to the desired substrate. The carrier film may include pigments, markings, text, designs, etc. on the surface opposite the composite adhesive, which are then fixedly attached to the surface of the substrate, or the carrier film may be free of such pigments and / or markings.

[0106] The thickness of the composite adhesive layer is typically at least 10 microns, 15 microns, 20 microns or even 25 microns (1 mil) and at most 50 microns, 60 microns, 70 microns, 80 microns, 90 microns, 100 microns or even 400 microns (16 mils) thick. In some embodiments, the thickness of the composite adhesive layer is not thicker than 100 microns, 150 microns or even 200 microns and at most 300 microns, 500 microns, 1000 microns, 1500 microns or even 2000 microns (80 mils) thick. The adhesive can be coated into a single layer or multiple layers.

[0107] In one embodiment, the composite adhesive of the present disclosure comprises at least 0.1 grams, 0.3 grams, 0.5 grams, 1 grams, 2 grams, 4 grams, 5 grams or even 10 grams of a plurality of polymer nanoparticles per 100 grams of (meth) acrylate-based matrix. In one embodiment, the composite adhesive composition comprises at most 10 grams, 15 grams, 20 grams, 25 grams, 30 grams, 35 grams or even 40 grams of a plurality of polymer nanoparticles per 100 grams of (meth) acrylate-based matrix. In one embodiment, the plurality of polymer nanoparticles are uniformly dispersed in the matrix, which can be visually observed by a smooth and clear composition without visible particle clusters.

[0108] Typically, the polymer nanoparticles are uniformly dispersed throughout the (meth)acrylate matrix in the adhesive layer, such as Figure 1 shown. Figure 1 A multilayer adhesive article is depicted, which includes an optional first substrate 12 and a second substrate 16, which can independently be an adherend, a liner, or a backing. Sandwiched between the two substrates is a composite adhesive layer 14, which includes a plurality of polymer nanoparticles 13 dispersed in a (meth)acrylate-based matrix 15. Alternatively, the polymer nanoparticles can be concentrated in one or more regions of the composite adhesive layer. For example, Figure 2 As shown, a plurality of polymer nanoparticles 23 in the (meth)acrylate-based matrix 24 are concentrated near one major surface of the composite adhesive layer 24 .

[0109] In one embodiment, the composite adhesive composition of the present disclosure is a pressure-sensitive adhesive. Pressure-sensitive adhesive compositions are well known to those of ordinary skill in the art and have properties including: (1) dry tack and permanent tack, (2) adhesion without exceeding finger pressure, (3) ability to remain on an adherend; and (4) sufficient cohesive strength. It has been found that materials that work well as pressure-sensitive adhesives are polymers that are designed and formulated to exhibit the desired viscoelastic properties, thereby achieving a desired balance of tack, peel adhesion, and shear holding power.

[0110] In one embodiment, the pressure-sensitive adhesive composition has a similar viscoelastic window defined by EP Chang, J. Adhesion, Vol. 34, pp. 189-200 (1991) such that the dynamic mechanical properties of the pressure-sensitive adhesive composition measured by known techniques fall within the following ranges measured at 25° C.:

[0111] G' measured at an angular frequency of 0.01 rad / s is greater than 1×10 3 Pa; and

[0112] G' measured at an angular frequency of 100 rad / s is less than 5×10 6 Pa.

[0113] The (meth)acrylate matrix, as another component of the adhesive composition, plays a bonding role between two adherends and may be tacky at room temperature or may not be tacky initially, but the adhesion strength increases over time.

[0114] In one embodiment, the composite adhesive composition of the present disclosure is a heat activated film adhesive wherein the film becomes tacky (ie, the Dahlquist standard for tack has a shear storage modulus of less than 0.3 MPa at an angular frequency of 1 Hz) when heated.

[0115] The disclosure has determined that the composite material comprising a plurality of particles dispersed in the (meth) acrylate matrix makes the adhesive composition have good impact resistance in resisting tensile impact force, and has good shear deformation resistance.Usually, adding a plurality of particles increases the shear storage modulus (G ') of the resulting composition.It is inferred that the shear storage modulus increases and is relevant to the shear deformation resistance of adhesive.In other words, adding a plurality of polymer nanoparticles makes the composite adhesive more "hard".Usually, it is believed that adding a (meth) acrylate macromonomer in the composition of the present disclosure reduces the shear storage modulus and Tg of the resulting composition, making the resulting composite adhesive have improved tensile peeling resistance, as demonstrated by the performance improvement in the random free fall test.As shown in the embodiment part, when using "softer" (meth) acrylate resin (that is, the shear storage modulus is lower than the resin of 80kPa or even 60kPa), adding a plurality of polymer nanoparticles increases the shear storage modulus, yet the random free fall test is affected. Therefore, the addition of (meth)acrylate macromers helps balance the stretch peel resistance, allowing these softer resins to resist not only tensile impact forces but also shear deformation.

[0116] In one embodiment, the composite adhesives disclosed herein have a shear storage modulus (G') of at least 100 kPa, 150 kPa, 200 kPa, 300 kPa, or even 400 kPa (kilopascals) at 25°C and 1 Hz.

[0117] In one embodiment, the composite adhesives disclosed herein have a peak stress in a dynamic shear test of at least 0.5 MPa, 0.7 MPa, 0.8 MPa, or even 0.9 MPa; and at most 2.0 MPa, 1.8 MPa, 1.7 MPa, 1.6 MPa, 1.5 MPa, 1.4 MPa, 1.3 MPa, 1.2 MPa, 1.1 MPa, or even 1.0 MPa.

[0118] In one embodiment, when tested and assembled as disclosed in a random free fall test, the composite adhesive disclosed herein was dropped 50 times at 1 meter without sample failure. In another embodiment, when tested and assembled as disclosed in a random free fall test, the composite adhesive disclosed herein was dropped 100 times at 1 meter without sample failure. In another embodiment, when tested and assembled as disclosed in a random free fall test, the composite adhesive disclosed herein was dropped 250 times at 1 meter without sample failure.

[0119] In one embodiment, the composite adhesive according to the present disclosure has good adhesion not only to substrates with high surface energy, but also shows good adhesion to low surface energy substrates. In one embodiment, when tested on a stainless steel substrate with an adhesive thickness of 8 mils (200 microns) according to ASTM D 3330 / D3330M, when laminated and peeled at room temperature, the adhesive of the present disclosure has a peel value greater than 0.4N / mm, 0.5N / mm, 0.6N / mm or even 0.8N / mm. The peel strength can be adjusted based on the required application, some of which require higher peel strength (e.g., at least 0.5N / mm, 0.6N / mm, 0.7N / mm or even 0.8N / mm, and up to 2.5N / mm, 2.2N / mm, 2.1N / mm or even 2.0N / mm).

[0120] In one embodiment, the composite adhesive disclosed herein is optically transparent. In one embodiment, the difference between the refractive index of a plurality of polymer nanoparticles and the refractive index of the (meth) acrylate matrix is ​​less than 0.2, 0.1 or even 0.05. The refractive index can be measured using techniques known in the art. For example, the Becker line method, in which a certified refractive index test liquid is used together with a microscope to measure the refractive index of a material, or the refractive index can be measured by using a refractometer and measuring the bend (sodium D line) of a 589nm wavelength in air at 25°C.

[0121] In one embodiment, the composite adhesive disclosed herein that comprises ionic liquid can experience electric induction adhesive stripping, wherein can apply voltage on whole adherend substrate as needed and strip the composite adhesive.Although do not wish to be limited by theory, it is believed that when applying voltage to the composite adhesive that comprises ionic liquid, ionic liquid is electrolyzed, wherein cation migrates to cathode side, and anion migrates to anode side, thereby weakens adhesive interface.Usually in order to carry out electrical stripping, the composite adhesive that comprises ionic liquid should be positioned between two conductive surfaces.For example, in one embodiment, Figure 1 The first substrate 12 and the second substrate 16 in the embodiment both contain conductive materials, forming an anode and a cathode, respectively, so as to perform electrical stripping. If the substrate is non-conductive or has a low conductivity (e.g., having a conductivity of at least 1×10 3 Ohm / square or even 5×10 3 ohm / square sheet resistance), another layer (such as a conductive coating) should be used to achieve electrical stripping. Figure 44, wherein the composite adhesive layer 44 is disposed between the first substrate 42 and the second substrate 46. The first conductive layer 41 is positioned between the first substrate 42 and the composite adhesive layer 44, and the second conductive layer 49 is positioned between the second substrate 46 and the composite adhesive layer 44. The first conductive layer and the second conductive layer can be the same material or can be different materials. The conductive layer can be a coating or layer. In another embodiment, the conductive layer is disposed within the composite adhesive layer, such as Figure 5 For example, in Figure 5 In the embodiment, the first conductive layer 51 is positioned between the composite adhesive layer 54a and the composite adhesive layer 54b, and the second conductive layer 59 is positioned opposite to the composite adhesive layer 54b.

[0122] In order to peel off as needed, the conductive surface (e.g., the first conductive layer 41 and the second conductive layer 49) is electrically coupled to a power source in a closable circuit or is electrically connected to a power source in a closable circuit. The power source can be a direct current power source providing a DC voltage in the range of about 3V to 250V, but other variations can also be considered. The amount of voltage applied can also be determined by the amount of time (e.g., 0.1 minutes or 1 minute to 5 minutes) for applying the voltage. For example, a higher voltage can be applied in a short time. An electric potential is applied between two opposite conductive surfaces (e.g., the first conductive layer 41 and the second conductive layer 49) to peel off one or both of the composite adhesive 44 and the conductive surfaces, so that the first substrate 42 can be separated from the second substrate 46. For example, although it is not desired to be bound by any particular theory, it is believed that the movement of ions in the composite adhesive can be affected by the electric potential applied to the composite adhesive. When a sufficient amount of movement is affected, such as when sufficient ionic components appear near the conductive surface, the bonding quality of the adhesive material is reduced, so that the conductive surface and / or the composite adhesive can be separated.

[0123] Exemplary conductive materials include: conductive carbonaceous materials or conductive metals. The conductive surface may comprise conventional materials such as metals, mixed metals, alloys, metal oxides and / or composite metal oxides, or the conductive surface may comprise conductive polymers. Examples of suitable metals for the conductive layer include metals from Group 1, metals from Groups 4, 5, and 6, and transition metals from Groups 8 to 10. Other examples of suitable metals for the conductive layer include stainless steel, Al, Ag, Mg, Ca, Cu, Mg / Ag, LiF / Al, CsF, and / or CsF / Al, and / or alloys thereof.

[0124] In some embodiments, the composite adhesive compositions described herein are suitable for bonding internal or external components of lighting display devices such as liquid crystal displays ("LCD") and light emitting diode ("LED") displays, such as mobile phones (including smart phones), wearable (e.g., wrist) devices, car navigation systems, global positioning systems, depth finders, computer monitors, laptop computers, and tablet computer displays, or for bonding objects (e.g., handles, display stands) to the exterior of electronic devices.

[0125] Example

[0126] Advantages and embodiments of the present disclosure are further illustrated by the following examples, but the specific materials and amounts thereof, as well as other conditions and details, described in these examples should not be construed as unduly limiting the present invention. Unless otherwise indicated, in these examples, all percentages, ratios and proportions are by weight.

[0127] Unless otherwise noted or apparent, all materials are commercially available from, for example, Sigma-Aldrich Chemical Company, Milwaukee, Wisconsin, or are known to those skilled in the art.

[0128] These abbreviations are used in the following examples: °C = degrees Celsius, cP = centipoise, g = gram, lb = pound, kg = kilogram, mL = milliliter, mol = mole, min = minute, cm = centimeter, Hz = Hertz, J = Joule, kDa = kilodalton, L = liter, mm = millimeter, mW = milliwatt, N = Newton, nm = nanometer, Pa = Pascal, rpm = revolutions per minute, ppm = parts per million, and wt = weight.

[0129] Table 1. Materials used to prepare the examples .

[0130]

[0131]

[0132] Test Method

[0133] Rheological properties and glass transition temperature

[0134] Both RF02N and RF12N liners were removed from the transfer tape samples and the composite adhesive was tested on a TA Instruments discovery hybrid rheometer III (DHR-3) (New Castle, DE, USA). The sample was heated from room temperature to 40°C at a rate of 3°C / min, then cooled to -50°C at a rate of 3°C / min, raised to 20°C, and then heated from 20°C to 140°C at a rate of 3°C / min. Data were collected during the second heating cycle at a 1 Hz oscillation frequency and strain values ​​in the linear viscoelastic regime (typically 1% to 5%). From the rheological curve diagram of G' and G" (y axis-1) versus temperature (°C) (x axis) and tan (δ) (y axis-2), the glass transition temperature (at 1 Hz) is determined as the peak of the tan (δ) curve. The peak (i.e., the highest value) in tan (δ) is selected from the y axis-2, and the corresponding temperature on the x axis is selected as the glass transition temperature. Tan (δ) is an abbreviation for the tangent value of the phase angle between the stress and strain oscillation waves in the shear rheology oscillation diagram. The sample that meets the rheological property requirements has a shear storage modulus (G')>100 kPa at 25°C.

[0135] Size Exclusion Chromatography (SEC)

[0136] Molecular weight (both number average molecular weight Mn and weight average molecular weight Mw) and polydispersity were determined using size exclusion chromatography with polystyrene standards. The chromatographic system included an instrument obtained under the trade name "ACQUITY" (Waters Corporation, Milford, MA, USA), and the following columns arranged in order (downstream): Styragel guard column (20 μm, 4.6 mm×30 mm), first Styragel HR 5E column (mixed bed, 5 μm, 7.8 mm×300 mm, 2K-4M), and second Styragel HR 5E column (all columns purchased from Waters Corporation). The analysis was performed using THF mobile phase at a flow rate of 1 mL / min.

[0137] Peel Adhesion Strength Test

[0138] For all peel adhesion tests, the RF02N release liner was removed from the transfer tape sample and the exposed adhesive side of the transfer tape was contacted to the plasma treated side of a 6 inch (15 cm) wide plasma treated polyester film (3M Company, 2 mil (50 μm) biaxially oriented PET film, the surface of which had been subjected to the plasma treatment conditions described in U.S. Pat. No. 10,134,566 (David et al.). A 6 inch (15 cm) rubberized hand roller (Polymag Tek, NY) was then placed over the construction and rolled by hand, ensuring that no air bubbles were trapped between the adhesive and the primed polyester film. Peel adhesion was measured at an angle of 180 degrees. Peel adhesion testing was performed on annealed 18 gauge 304 stainless steel (SS) test panels purchased from Chem. Instruments, Fairfield, OH. The RF12N release liner was removed from the PET backing of the tape and the exposed adhesive side was laminated directly to a 2 inch × 6 inch (5.08 cm × 15.24 cm) stainless steel test panel using a weighted rubberized (4.5 lb, 2.04 kg) hand roller for 3 seconds each time, repeated 4 times. Before the peel test, the transfer tape, stainless steel test panel, and the transfer tape applied to the stainless steel test panel were placed in a temperature and humidity controlled (CTH) room (set at 23 ° C, 50% RH (relative humidity)) for conditioning. Before and after the test, the SS test panel was cleaned with methyl ethyl ketone (MEK). The peel test was performed using SP-2100iMass (iMass Inc., Accord, MA USA) at a rate of 12 inches / minute (0.3 m / min). Each sample was peeled off from the same substrate at least three times, and the average of all three measurements was recorded. The peel adhesion and failure mode were recorded. All samples exhibited adhesive failure (ie, failure between the adhesive and the SS panel) except for the sample marked as breaking between the adhesive and the polyester film.

[0139] Dynamic shear test

[0140] For dynamic shear testing, a modified version of "ASTM D1002-2019 – Apparent Shear Strength of Adhesive-Bonded Metal Specimens in Single Lap Joints" was used. The adhesive was tested for shear between the ends of two overlapping 304 stainless steel (SS) panels (1 inch (2.5 cm) wide by 4 inches (10.1 cm) long by 1 / 16 inch (1.6 mm) thick with an overlapping adhesive bond area of ​​1 inch (2.5 cm) by 1 inch (2.5 cm)). To prepare the test specimens, a 1 inch (2.5 cm) by 1 inch (2.5 cm) square sample of the designated transfer tape was cut and the RF02N liner was removed and the exposed adhesive side of the transfer tape was laminated to the end of one of the SS panels at room temperature. The RF12N liner was then removed from the transfer tape bonded to the first SS panel and the exposed adhesive was bonded to the second SS panel to ensure an overlap area of ​​1 inch (2.5 cm) by 1 inch (2.5 cm). The bonded laminates were then weighed at room temperature with a 50 lb (22.7 kg) weight applied to a 1 inch (2.5 cm) x 1 inch (2.5 cm) adhesive bonding area for 30 seconds and allowed to hold at room temperature for a minimum of 1 day. After the hold time, the adhesive joints were tested by clamping the opposite ends of the stainless steel substrate in a load frame (MTS, Eden Prairie, MN) and the test was conducted at a displacement rate (vertical grip speed) of 10 mm / min. The maximum peak in the stress of the stress-strain curve was used to determine the peak stress of the adhesive sample in the dynamic shear test.

[0141] Random free fall test

[0142] like Figure 3A (top view) and Figure 3B (sectional view), a random free fall test was performed on a Heina rotating drum tester II (Heina, Halikko, Finland). Figure 3AAs shown, two adhesive strips 35 are used to adhere a polycarbonate panel 34 to a test frame 32. The adhesive strips are 2 mm wide. The base of the polycarbonate test frame (purchased from Chem Instruments, Fairfield, OH, USA) is 6.25 inches (15.8 cm) long × 3.25 inches (8.3 cm) wide × 0.375 inches (9.5 mm) thick. The test frame has a raised portion along each short side edge (about 0.25 inches (0.63 cm) high from the base) that is designed to contact the surface of the drum tester and prevent direct contact with the polycarbonate panel and the drum tester surface. The polycarbonate panel is 5.125 inches (13 cm) long × 2.875 inches (73 cm) wide × 0.125 inches (3.2 mm) thick. Test sample is prepared as follows: use 2mm wide tape cutter to cut adhesive transfer tape into 3.25 inches (8.3cm) long × 2mm wide. RF02N peel liner is removed from each strip of transfer tape, and the exposed adhesive side is laminated to the test frame so that the adhesive is placed parallel to each opposite edge 1 inch (2.5cm) from the test frame. Then RF12N liner is removed from each adhesive strip, and the polycarbonate panel is laminated to the test frame using the adhesive strip that adheres, ensuring that the panel is at a fixed distance from each raised portion of the test frame. 4kg weight is placed on the length of each adhesive strip of tape, and the third 4kg weight is placed on the top of the other two weights. Weight is maintained on tape for 30 seconds, and then the bonded test sample is placed in CTH room for 3 days. Then the bonded test sample is placed in Heina rotary drum tester, and is repeatedly dropped from the height of 1m at a rate of 12 drops per minute. The drops before failure (as indicated by bursting from one or both sides of the polycarbonate panel of the polycarbonate test frame) were counted. The sample was dropped 250 times. A result of 250 means that the sample withstood 250 drops.

[0143] Corrosion testing

[0144] To prepare the test specimens, a 1 inch (2.5 cm) x 1 inch (2.5 cm) square sample of the designated transfer tape was cut, the RF02N liner was removed, and the exposed adhesive side of the transfer tape was laminated to a 2 mil (50 micrometer) thick polyethylene terephthalate (PET) panel at room temperature. The RF12N liner was then removed from the transfer tape bonded to the PET panel and the exposed adhesive was hand rolled down onto a copper foil sheet. The test specimens were placed in an oven set at 65°C and 90% relative humidity (RH). The specimens were removed from the oven and evaluated for signs of corrosion (discoloration of the copper foil) on the 1st, 3rd, and 7th days. The specimens were then scored on a scale of 1 to 3, where 1 = no signs of corrosion, 2 = less than or equal to 25% of the copper foil area had corrosion, and 3 = greater than 25% of the copper foil area had visible corrosion.

[0145] Electrostripping

[0146] A tensile push-out device was used, which included a stainless steel coupon (40 mm x 40 mm x 3 mm) containing a circular hole (diameter = 24 mm) in the center and a circular stainless steel elastic disk (diameter = 33 mm, thickness 3 mm). The specified transfer tape was punched into a ring with an outer diameter of 31 mm and an inner diameter of 26 mm. The RF02N liner was removed and the exposed adhesive side of the transfer tape ring was laminated around the circular hole on the stainless steel coupon. The RF12N liner was then removed from the transfer tape bonded to the coupon and the exposed adhesive was bonded to the stainless steel elastic disk so that the elastic disk covered the hole in the coupon. The test sample was weighed with an 8 kg weight at 23°C for 30 seconds and then the test sample was removed. The test sample was then kept at 23°C / 50%RH for at least 2 days before testing. A power supply (1685B series, purchased from B&K Precision, Yorba Linda, CA) was then connected to the push-out device with the positive electrode connected to the spring disk and the negative electrode connected to the specimen block. Unless otherwise specified, a voltage of 50 volts was applied to the entire specimen block and spring disk for 180 seconds. After the voltage was applied for 180 seconds, the electrodes were immediately disconnected from the test sample and the test sample was loaded onto an electromechanical tester (MTS Criterion Model C43, Eden Prairie, MN). The stainless steel specimen block was held in place while a 0.75 inch (19 mm) diameter rod from the electromechanical tester was positioned through the circular hole in the stainless steel specimen block to contact the circular stainless steel spring disk. The electromechanical tester was used to push the spring disk away from the specimen block at a rate of 10 mm / min under ambient conditions. The peak stress required to remove the spring disk from the specimen block was recorded in MPa (megapascals). Test specimens with no voltage applied were also tested in this manner. The initial push out peak stress (ie, when no voltage was applied prior to testing) and the % reduction in push out peak stress after 50 volts were applied to the entire test specimen for 3 minutes (or 180 seconds) are reported in Table 11.

[0147] Slurry polymer preparation

[0148] Slurries SRP-1 to SRP-3 were synthesized by adding the monomers (as specified in Table 2) together at the appropriate loading weight %, adding IRG 651 (0.02 grams relative to 100 grams of total monomers), and exposing the monomer solution to 0.3 mW / cm2 UV-LED irradiation (365 nm) until the mixture had a high viscosity (about 1,000 cP). The molecular weight in megadaltons (MDa) as determined by the SEC test method described above, as well as the polydispersity of the resulting slurries are shown in Table 3.

[0149] Table 2. Monomer composition used to make syrup polymer, in wt %

[0150] Slurry 2-EHA 2-MBA C18A HBA nB NNDMA toACM NVP AA HDDA SRP-1 35 35 - - - 25 5 - - - SRP-2 - - 98 - - 2 - - - - SRP-3 80 - - 20 - - - - - - SRP-4 90 - - - - - - - 10 - SRP-5 - - - - 90 - - - 10 - SRP-6 70 - - - - - - 30 - - SRP-7 - - - - 70 - - 30 - - SRP-8 - - - - 80 - - 20 - - SRP-9 65 - - - - 30 5 - - 0.02*

[0151] *Added in phr (amount expressed as parts per hundred parts of resin relative to 100 parts of the total amount of other monomers).

[0152] Synthesis of dimethylaminoethyl acrylate methylbis(fluorosulfonyl)imide. (DMAEAMFSI)

[0153] DMAEAM Cl (125 g of 80 wt % aqueous solution, 516 mmol monomer) was added to a round bottom flask equipped with a polytetrafluoroethylene coated stirring bar. The solution was then diluted with 100 g of water and Li FSI (100 g, 533 mmol) was slowly added to the solution while stirring. When Li FSI was added, an organic phase was formed and separated from the aqueous phase. After 24 hours, the organic phase was separated from the aqueous phase using a separatory funnel. The organic phase was washed with water (3×100 mL). The organic phase was dried by rotary evaporation to obtain 85.2 g of DMAEMAM FSI.

[0154] Dimethylaminoethyl acrylate methyl tricyanomethyl (DMAEAM Synthesis of TCM

[0155]

[0156] DMAEAM Cl (50g 80 % by weight aqueous solution, 206.5mmol monomer) is added in the round-bottomed flask equipped with the stirring rod coated with polytetrafluoroethylene.Then, dilute the solution with 100g water, and in this solution, slowly add Na TCM (23.4g, 206.5mmol) while stirring.After stirring for 14 days, the solution is added in 3.5L acetone to precipitate NaCl.The solution is left standstill overnight, and then filtered through diatomite.Remove acetone via rotary evaporation, obtain yellow liquid. 1 H-NMR (500 MHz; acetone-d6): δ 6.42 (dd, J = 17.3, 1.3 Hz, 1H), 6.21 (dd, J = 17.3, 10.5 Hz, 1H), 5.97 (dd, J = 10.5, 1.3 Hz, 1H), 4.72 (dq, J = 7.2, 2.5 Hz, 2H), 3.99-3.97 (m, 2H), 3.44 (s, 9H). 13-C NMR (126 MHz; acetone): δ 164.8, 131.7, 127.8, 120.9, 64.9, 58.0, 53.7, 4.8 Nuclear magnetic resonance (NMR) was performed on a Bruker 500 MHz using acetone-d6 as solvent. The sample was prepared at a concentration of 10 wt%. For 1-H NMR, the acetone reference was 2.05 ppm. For 13-C NMR, the acetone reference was 29.84 ppm.

[0157] Table 3. Molecular weight data of the resulting syrup polymer from Table 2

[0158]

[0159] Molecular weight (M w ) greater than 8 million g / mol, sample outside the calibration standard. NT = not tested.

[0160] Example 1 to Example 11 (E1-E11) and Comparative Example 1 to Comparative Example 10 (CE1-CE10)

[0161] The curable compositions were made using the components listed in Table 4. The designated syrups were used at 100 parts and the remaining components were added in the amounts listed (eg, 5 g PEG-A was added to 100 g SRP-1 in E1).

[0162] Each curable composition was then coated between two release liners (RF12N and RF02N). The samples were then cured under 405 nm UV-LED light with a total dose of 3.1 J / cm2, measured using a radiometer equipped with a high power sensor head (available from EIT Incorporated, Sterling, VA, under the trade designation "POWER PUCK II") to give a transfer tape having an 8 mil (200 μm) thick adhesive layer.

[0163]

[0164] Table 5. Rheological properties of adhesive compositions

[0165]

[0166] Table 6. 180 degree peel adhesion, dynamic shear and random free fall data for transfer tapes

[0167]

[0168]

[0169] NT = Not Tested

[0170] Table 7. Summary of test results

[0171]

[0172] NT = Not Tested

[0173] Example 12 to Example 21 (E12-E21) and Comparative Example 11 to Comparative Example 15 (CE11-CE15)

[0174] Curable compositions were made to test the corrosion and electrostripping properties of the adhesive using the components listed in Table 8. The specified syrups were used at 100 parts and the remaining components were added in the amounts listed (e.g., 5 g PEG-A was added to 100 g SRP-1 in E12).

[0175] Each curable composition was then coated between two release liners (RF12N and RF02N). The samples were then cured under 405 nm UV-LED light at a total dose of 3.1 J / cm2, measured using a radiometer equipped with a high power sensor head (available from EIT Inc., Sterling, Virginia, USA under the trade designation "POWER PUCK II") to give a transfer tape having an 8 mil (200 μm) thick adhesive layer.

[0176]

[0177] Table 9. Rheological properties of adhesive compositions

[0178]

[0179] Table 10. 180 degree peel adhesion, dynamic shear and random free fall data for transfer tapes

[0180]

[0181] NT = Not Tested

[0182] Table 11. Electrostripping

[0183]

[0184] * Voltage is maintained for 5 minutes instead of 3 minutes

[0185] Table 12. Corrosion results

[0186]

[0187] Table 13. Summary of results

[0188]

[0189] Foreseeable modifications and alterations of the present invention will be apparent to those skilled in the art without departing from the scope and spirit of the present invention.The present invention should not be limited to the embodiments shown in this application for illustrative purposes.

Claims

1. A polymerizable composition comprising: (i) a polymerizable matrix comprising: (a) a (meth)acrylate macromonomer, wherein the (meth)acrylate macromonomer comprises a poly(ethylene oxide) group, a poly(propylene oxide) group, a poly(ethylene oxide-co-propylene oxide), a poly(tetramethylene oxide) group, or a combination thereof; (b) C1 to C 12 One or more of (meth)acrylate monomers; (c) a cross-linking agent; and (d) 0 to up to 7 wt % of a hydroxyl-containing (meth)acrylate monomer; and (ii) a plurality of polymer nanoparticles, wherein the polymer nanoparticles comprise an interior region and an outer shell, the interior region comprising a polymer having a glass transition temperature below room temperature, and the outer shell comprising a polymer having a glass transition temperature of at least 50°C.

2. The composition of claim 1, wherein the plurality of polymer nanoparticles have an average particle size of less than 800 nanometers.

3. The composition of any one of the preceding claims, wherein the plurality of polymer nanoparticles have an average particle size of at least 50 nanometers and at most 300 nanometers.

4. The composition of any one of the preceding claims, wherein the plurality of polymer nanoparticles are core-shell nanoparticles.

5. The composition of claim 4, wherein the core-shell nanoparticles comprise a core comprising polybutadiene or poly(butadiene-co-styrene).

6. The composition of claim 4, wherein the core-shell nanoparticles comprise a core comprising a (meth)acrylic acid polymer.

7. The composition of any one of claims 4 to 6, wherein the core-shell nanoparticles comprise a shell comprising poly(methyl methacrylate).

8. The composition of any one of claims 4 to 7, wherein the core-shell nanoparticles comprise methacrylate-butadiene-styrene.

9. The composition of any one of claims 4 to 8, wherein the core-shell nanoparticles have a core:shell ratio between 90:10 and 10:

90.

10. The composition of any one of the preceding claims, wherein the composition comprises at least 0.1 wt% and at most 40 wt% of the plurality of nanoparticles based on the polymerizable matrix.

11. The composition of any preceding claim, wherein the polymerizable matrix comprises up to 60 wt% of the (meth)acrylate macromer.

12. The composition of any preceding claim, wherein the (meth)acrylate macromonomer has a number average molecular weight of no greater than 10,000 Daltons.

13. The composition of any one of the preceding claims, wherein the (meth)acrylate macromonomer has a number average molecular weight in the range of 350 to 10,000 Daltons.

14. The composition of any preceding claim, wherein the (meth)acrylate macromonomer comprises a poly(ethylene oxide) group.

15. A composition according to any one of the preceding claims, wherein the C1 to C 12 The (meth)acrylate monomer includes one of the following: 2-methylbutyl acrylate, 2-ethylhexyl acrylate, butyl acrylate, isooctyl acrylate, or a combination thereof.

16. A composition according to any one of the preceding claims, wherein the polymerizable matrix comprises at least 10 wt % to at most 99.5 wt % of the C1 to C 12 (Meth)acrylate monomers.

17. The composition of any preceding claim, wherein the polymerizable matrix further comprises acrylic acid.

18. The composition of any one of the preceding claims, wherein the crosslinking agent is selected from one of the following: a triazine, a multifunctional (meth)acrylate, or a combination thereof.

19. The composition of any preceding claim, wherein the polymerizable matrix comprises 0.01 to 5 parts (solids / solids) of the crosslinker.

20. The composition of any preceding claim, wherein the composition is substantially free of solvent.

21. The composition of any one of claims 1 to 19, wherein the composition comprises a solvent.

22. The composition of any preceding claim further comprising an ionic liquid.

23. The composition of claim 22, wherein the ionic liquid comprises at least one of a nitrogen-containing cation, a phosphonium ion, or a sulfonium ion cation.

24. The composition of any one of claims 22 to 23, wherein the ionic liquid comprises at least one of a sulfate, sulfonate, carboxylate, phosphate, borate, imide, sulfonimide, imide, or halide anion.

25. The composition of any one of claims 22 to 24, wherein the ionic liquid does not contain carbon-fluorine bonds, optionally wherein the ionic liquid is dimethylaminoethyl acrylate methylbis(trifluoromethanesulfonyl)imide.

26. The composition of any one of claims 22 to 25, wherein the ionic liquid does not contain fluorine atoms, optionally wherein the ionic liquid is dimethylaminoethyl acrylate methyl tricyanomethide.

27. The composition of any preceding claim, wherein the composition is a coatable resin.

28. An at least partially polymerized reaction product of a polymerizable composition according to any one of the preceding claims.

29. An adhesive article comprising an adhesive composition derived from the polymerizable composition of any one of claims 1 to 25, wherein the adhesive composition is disposed on a substrate.

30. The adhesive article of claim 29, wherein the adhesive composition has a shear storage modulus of at least 100 kPa at 25°C and 1 Hz.

31. The adhesive article of any one of claims 29 to 30, wherein the adhesive article passes a random free fall test after 50 drops.

32. The adhesive article of any one of claims 29 to 31, wherein the adhesive article has a dynamic shear of at least 0.5 MPa.

33. The adhesive article of any one of claims 29 to 32, wherein the substrate is a backing.

34. The adhesive article of claim 33, further comprising a second adhesive layer, wherein the backing is disposed between the adhesive composition and the second adhesive layer.

35. The adhesive article of any one of claims 29 to 34, wherein the substrate is a liner comprising a release agent.

36. The adhesive article of any one of claims 29 to 35, wherein the adhesive article is a tape or a label.

37. The adhesive article of any one of claims 29 to 36, wherein the adhesive composition is a layer having a first thickness, and the plurality of polymer particles have an average particle size less than the first thickness.

38. A method of making an adhesive article, the method comprising: (i) obtaining a polymerizable matrix, the polymerizable matrix comprising: (a) a (meth)acrylate macromonomer, wherein the (meth)acrylate macromonomer comprises a poly(ethylene oxide) group, a poly(propylene oxide) group, a poly(ethylene oxide-co-propylene oxide), a poly(tetramethylene oxide) group, or a combination thereof; (b) C1 to C 12 One or more of (meth)acrylate monomers; (c) a cross-linking agent; as well as (d) 0 to up to 7 wt % of a hydroxyl-containing (meth)acrylate monomer; and (ii) adding a plurality of polymer nanoparticles to the polymerizable matrix to form a composition.

39. The method of claim 38, comprising at least partially polymerizing the polymerizable matrix to form an at least partially polymerized composition prior to adding the plurality of polymer nanoparticles.

40. The method of any one of claims 38 to 39, further comprising curing the composition.

41. The method of claim 40, wherein the curing is performed by ultraviolet radiation.

42. The method of any one of claims 38 to 41, wherein the adhesive article is contacted with a substrate.

43. A method of separating an adhesive article, the method comprising: (I) providing an adhesive composite adhesively attached between two conductive substrates, wherein the adhesive composite comprises: (i) A substrate derived from: (a) a (meth)acrylate macromonomer, wherein the (meth)acrylate macromonomer comprises a poly(ethylene oxide) group, a poly(propylene oxide) group, a poly(ethylene oxide-co-propylene oxide), a poly(tetramethylene oxide) group, or a combination thereof; (b) C1 to C 12 One or more of (meth)acrylate monomers; (c) a cross-linking agent; as well as (d) 0 to up to 7% by weight of hydroxyl-containing (meth)acrylate monomers; (ii) a plurality of polymer nanoparticles, wherein the polymer nanoparticles comprise an interior region and an outer shell, the interior region comprising a polymer having a glass transition temperature below room temperature, and the outer shell comprising a polymer having a glass transition temperature of at least 50° C.; and (iii) ionic liquids; (II) applying an electric potential between the two conductive substrates; as well as (III) separating the two conductive substrates after applying the potential.

44. A compound according to the formula:

Citation Information

Patent Citations

  • Block copolymer, method of making the same, diamine precursors of the same method, method of making such diamines and end products comprising the block copolymer

    EP0250248B1

  • Improved impact modified thermoplastic composition

    EP2465882B1

  • Method of making a nanostructure and nanostructured articles

    US10134566B2

  • Liners and adhesive tapes having low adhesion polyvinyl carbamate coatings

    US2532011A

  • Epoxypolysiloxane release coatings for adhesive materials

    US4313988A